2015
DOI: 10.1111/ocr.12091
|View full text |Cite
|
Sign up to set email alerts
|

The impact of dental appearance and anxiety on self‐esteem in adult orthodontic patients

Abstract: Anxiety plays a fundamental role in the effect of perceived dental impact on self-esteem in adult patients undergoing orthodontic treatment. These results have important practical implications for the design of bio-psycho-social intervention programs that contemplate cognitive-affective variables as an essential part of orthodontic treatment in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(48 citation statements)
references
References 48 publications
3
13
0
1
Order By: Relevance
“…The present study observed a negative correlation between self-esteem and social impact, psychological impact and aesthetic concern, which is corroborated by other studies ( 16 , 26 ). In contrast, the correlation was positive between self-esteem and the PIDAQ questionnaire’s self-confidence subscale; in other words, dental satisfaction has a positive effect on self-esteem ( 1 , 16 , 26 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The present study observed a negative correlation between self-esteem and social impact, psychological impact and aesthetic concern, which is corroborated by other studies ( 16 , 26 ). In contrast, the correlation was positive between self-esteem and the PIDAQ questionnaire’s self-confidence subscale; in other words, dental satisfaction has a positive effect on self-esteem ( 1 , 16 , 26 ).…”
Section: Discussionsupporting
confidence: 93%
“…On examining the results by gender, it was found that the men had lower self-esteem and consequently their dental aesthetics had a greater impact (divergent relationship), whereas in other studies ( 16 ) it was the women who placed great importance on dental aesthetics. A study by Jung ( 27 ) observed that the girls were generally less self-confident than the boys, in contrast to the present findings.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Thus, a more individualised treatment plan can be established, meeting the expectations of the patient. Some studies have shown that sex 10,11,15–19 and age 12,19 may affect the impact of dental aesthetics, however, other authors did not find this relationship 7,8,20,21 . Regarding clinical characteristics, studies indicate that more compromised dental aesthetics have greater psychosocial impact 7,8,16,18,20 .…”
Section: Introductionmentioning
confidence: 99%